Multiple Facets of Borderwork. Urban Actors Between Migrants' Struggles and State Control. (2nd January 2023) - Fauser, Margit; Di Stefano, Corinna A.; Fattorelli, Elena
ABSTRACT: In this article, we investigate the roles of urban actors supporting migrants' struggles and confronting state control, focusing on the fields of family reunification and access to health care in the city of Frankfurt am Main. We bring together insights from border studies, street-level theory, and social policy and social work literature to elaborate on the notions of 'urban border space' and borderwork to offer a new theorisation on 'where the border is' and 'who makes the border'. Multiple transformations that have taken place in border control and the welfare state regime have led to diverse engagement on the part of civil society towards migrants, particularly in cities. City authorities, in turn, enforce the border, yet also respond to migrants' exclusion. Here, devolution and collaboration between city and civil society organisations have partly blurred the line between different types of urban actors. Our analysis identifies four roles within urban actors' borderwork – brokerage, advocacy, direct care and gatekeeping –, each of which is associated with a different relationship with state migration control. We thus argue that the supposed dichotomous relationship between state (re-)bordering and civil society de-bordering is too simplistic and that urban actors' roles in borderwork are instead multifaceted.